2013
DOI: 10.3389/fgene.2013.00080
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Protein 53-Induced Nuclear Protein 1 Enhances p53 Function and Represses Tumorigenesis

Abstract: Tumor protein 53-induced nuclear protein 1 (TP53INP1) is a stress-induced p53-target gene whose expression is modulated by transcription factors such as p53, p73, and E2F1. TP53INP1 gene encodes two isoforms of TP53INP1 proteins, TP53INP1α and TP53INP1β, both of which appear to be key elements in p53 function. In association with homeodomain-interacting protein kinase-2 (HIPK2), TP53INP1 phosphorylates p53 protein at Serine-46. This enhances p53 protein stability and its transcriptional activity, leading to tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 53 publications
4
65
0
Order By: Relevance
“…However, given the established role of the tumor protein p53 in B-cell differentiation and lymphomagenesis, 56 it is intriguing that 3 of the FOXP1-repressed proapoptotic genes (ie, encoding TP63, TP53INP1, and RASSF6) are tumor suppressors that share the capacity to enhance p53 activity. [57][58][59] Apart from that, p63 expression has been correlated to DLBCL prognosis, 60,61 expression of TP53INP1 is low in MALT lymphomas, 62 and methylation of the RASSF6 promoter has been observed in B-cell acute lymphoid leukemia and chronic lymphoid leukemia. 63,64 Although further studies are needed to determine if and how these proapoptotic genes control B-cell survival and lymphomagenesis, combined the 7 FOXP1-repressed proapoptotic genes clearly have prognostic significance for overall and progression-free survival of DLBCL patients ( Figure 1D); the patients with low expression of the gene signature always have a worse prognosis, which is completely in line with their proapoptotic function and with a potential role in lymphomagenesis.…”
Section: Discussionmentioning
confidence: 99%
“…However, given the established role of the tumor protein p53 in B-cell differentiation and lymphomagenesis, 56 it is intriguing that 3 of the FOXP1-repressed proapoptotic genes (ie, encoding TP63, TP53INP1, and RASSF6) are tumor suppressors that share the capacity to enhance p53 activity. [57][58][59] Apart from that, p63 expression has been correlated to DLBCL prognosis, 60,61 expression of TP53INP1 is low in MALT lymphomas, 62 and methylation of the RASSF6 promoter has been observed in B-cell acute lymphoid leukemia and chronic lymphoid leukemia. 63,64 Although further studies are needed to determine if and how these proapoptotic genes control B-cell survival and lymphomagenesis, combined the 7 FOXP1-repressed proapoptotic genes clearly have prognostic significance for overall and progression-free survival of DLBCL patients ( Figure 1D); the patients with low expression of the gene signature always have a worse prognosis, which is completely in line with their proapoptotic function and with a potential role in lymphomagenesis.…”
Section: Discussionmentioning
confidence: 99%
“…TP53INP1 was reported to be downregulated in diverse types of cancer and the decreased expression of TP53INP1 was shown to contribute to the pathogenesis of cancer (26)(27)(28). TP53INP1 therefore has potential as a therapeutic target for cancers.…”
Section: Mir-96 Directly Regulates Tp53inp1 Foxo1 and Foxo3a Expressmentioning
confidence: 99%
“…Data in Fig. 4B indicate phosphorylation of the Ser9 and Ser15 residues (both trigger p53 activity to induce DNA repair pathways in response to DNA damage (Haas, 2009; Oda et al, 2000; Shahbazi et al, 2013; Xu et al, 2012; Yamaguchi et al, 2001)), as well as Ser46, whose phosphorylation regulates the ability of p53 to induce apoptosis (Oda et al, 2000). The western blot analysis showed that X-ray IR induced phosphorylation of all analyzed serine residues in both HIV-1 chronically infected and parental uninfected cells.…”
Section: Resultsmentioning
confidence: 97%
“…In fact, we have observed presence of Tat after IR when transfecting an epi-Tat construct into lymphocytes (CEM) following IP/WB for presence of Tat after 48 h (data not shown). IR-induced p53 phosphorylation at Ser15 and Ser20 are utilized for DNA repair and release, whereas Ser46 phosphorylation is critical for apoptosis (Haas, 2009; Shahbazi et al, 2013; Yamaguchi et al, 2001). Western blot analysis of chronically-HIV-1 infected T cell line and parental uninfected cells revealed involvement of the mechanism of p53-dependent apoptosis in both infected and uninfected irradiated cells, with the level of phosphorylation of Ser46 residue markedly higher on the p53 protein from infected cells.…”
Section: Discussionmentioning
confidence: 99%